Handbook of military and defense operations research - Scala, Natalie M.; Howard, James P., II (James Patrick) (Boca Raton, FL : CRC Press, 2020)
Operations research (OR) is a core discipline in military and defense management. Coming to the forefront initially during World War II, OR provided critical contributions to logistics, supply chains, and strategic simulation, while enabling superior decision-making for Allied forces. OR has grown to include analytics and many applications, including artificial intelligence, cybersecurity, and big data, and is the cornerstone of management science in manufacturing, marketing, telecommunications, and many other fields. The Handbook of Military and Defense Operations Research presents the voices leading OR and analytics to new heights in security through research, practical applications, case studies, and lessons learned in the field. Features Applies the experiences of educators and practitioners working in the field Employs the latest technology developments in case studies and applications Identifies best practices unique to the military, security, and national defense problem space Highlights similarities and dichotomies between analyses and trends that are unique to military, security, and defense problems
OCLC-licensed vendor bibliographic record.
Keywords: Military art and science; Operations research; BUSINESS & ECONOMICS / Operations Research; MATHEMATICS / General; MATHEMATICS / Probability & Statistics / General